Technical change and profits: the prisoner's dilemma - Baldani, Jeffrey; Michl, Thomas R. (2000)
We examine the implications of biased-lower marginal, but higher fixed, cost - technical change in a model of oligopoly. Such changes create an incentive for firms to adopt new technologies in a quest for increased output, market share, and profits. These individual incentives lead to a prisoner's dilemma: the increase in firms' outputs causes market price to fall. The analysis specifies conditions under which the decrease in price will result in lower profits for both the individual firms and the industry as a whole. - Reproduced
Keywords: Technological change; Marxism; Profits